Experimental giardiasis in goat kids - Koudela, B; Vítovec, J (Veterinary parasitology, 1998)
The clinical, pathological and parasitological features of giardiasis resulting from experimental inoculation with 3 x 10(6) Giardia cysts were studied in goat kids. All experimentally inoculated goat kids given Giardia cysts became infected. Three of the eight inoculated kids had decreased appetite, formless feces and become slightly depressed beginning 7 or 8 days post inoculation. The mean duration of the appearance of abnormal feces was 6 days. Irregular and intermitted cysts shedding started after prepatent periods of 6-10 days and lasted throughout this study (10 weeks). The evidence of high infectivity and fast transmission of Giardia were observed under standard zoohygienic conditions. The characteristics of intestinal lesions were similar to those found in other hosts infected with Giardia. The most severe lesions were seen in the duodenum and proximal jejunum, and consisted of moderate villus atrophy, villus blunting, crypt hyperplasia and inflammatory infiltration in the lamina propria. Scanning electron microscopy revealed ultrastructural alterations in the microvillus border of enterocytes. Mucosal smears and histological sections of the gall bladder displayed Giardia trophozoites and gall bladder epithelium hyperplasia together with bile ductular proliferation in the liver tissue in two kids.
Keywords: Giardia; Microvilli; mikroklky; feces; Gerbillinae; giardiáza; kozy; jejunum; Swine Diseases; Female; střevní sliznice; nemoci koz; Goat Diseases; Microscopy, Electron, Scanning; Jejunum; zvířata; Giardiasis; Swine; Feces; ženské pohlaví; Male; Goats; mikroskopie elektronová rastrovací; nemoci prasat; Animals; mužské pohlaví; Intestinal Mucosa; prasata